Spatial integration and price transmission in selected cassava products markets in Nigeria: a case of gari - Ojiako, I.; Ezedinma, C.I.; Asumugha, G.N.; Okechukwu, R.U. (2013)
An advanced time series econometric technique was used to study the interaction between the prices of fermented flour, a popular cassava-based food product also called lafun, in typical urban-demand and ruralsupply markets in Nigeria. The price data cover 95 weeks from week 37 of 2004 to week 28 of 2006. The Augmented Dickey-Fuller (ADF) test was used to investigate stationarity in the pairs of prices while the Johansen cointegration technique, with its associated vector error correction model (VECM), was used to measure the speed of adjustment coefficients characterizing the long run dynamics of the system. Individual unit roots tests revealed non-stationarity in the price series - rural and urban prices were integrated of order one. The ADF-test statistics for the rural and urban prices were -1.42 and -2.46 in levels and -9.67 and -10.75 in first differences. The pair of prices was cointegrated with highly significant trace-statistics (16.41; p<0.5). The VECM reveals that the long-run equilibrium after exogenous shocks in the markets were restored primarily by corrections made by the urban market prices. The Granger causality runs one-way from the rural to the urban market, without a feedback loop. Also, the impulse response analysis revealed that the rural price was more responsive to shocks emanating from the rural market, the effect of which was computed as 95.6% using the forecast error variance decompositions. Results revealed further that the effects of rural prices’ shock on urban price was very negligible at 3.2% after 10 weeks. The implication is that the rural market was the dominant market for determining the price of lafun in the short-run. The error correction model revealed significant causality link between the peripheral and central markets, suggesting a clear trend in price leadership. It follows that there could be efficiency in transmission of price information among operators if relative stability is attained in the rural markets of lafun in Nigeria. The study recommends that farmers should be placed at the centre of the marketing policy to enable them determine the direction of price movements.